Effect of Feeding Different Dietary Levels of Rice Distiller’s Dried Grains with Solubles (RDDGS) on Growth Performance of Commercial Broiler Chicken - N Patel, Apal; S Joshi, Rajesh; P Savaliya, Fulabhai; B Patel, Atul; J Bhagora, Nikesh; R Devalia, Bharat (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A by-product of ethanol manufacturing, Rice Distillers Dried Grains with Solubles (RDDGS), is utilized as an alternate protein source in  poultry diets. The current investigation was carried out over a duration of six weeks to examine the effect of feeding different dietary  levels of RDDGS on growth performance of commercial broiler chicken. A total of 144 straight-run day-old commercial broiler chicks  were randomly distributed to six treatments. Each treatment group consisted of four replicates and in each replicate, six chicks were  there, leading to 24 chicks per treatment. The experimental diets consisted of Control basal diet (T1), and the diets T2 to T6 with 5, 10,  15, 20 and 25% RDDGS, respectively. The body weight of birds fed basal diet (T1) was significantly (p
Keywords: Commercial broiler chicken; Growth performance; Protein source; RDDGS; ROFC